Produção e comercialização em assentamentos de reforma agrária do MST: pesquisa participativa e pesquisa-ação em Pernambuco e no Rio Grande do Sul - Betanho, Cristiane (2008)
Looking for to legitimize their action the landless country laborers movement has been offering part of the nestings production to the society, it is one way that they found for that. The nestings agriculturists has organizing in association and cooperatives looking for working together can be stronger producing and commercializing instead of producing the capital surplus in any cost as capitalism idea. By the other hand, most part of the production in general raw materials and product in nature with low aggregated value realized has been commercialized by the brokers or executives who add value and take the under values generated by this activity. This research had two objectives: a) analyse the limits and possibilities on the production and on the commercialization in ten enterprises created and administrated for the Rio Grande do Sul and Pernambuco nestings by the participative research and b) to present the process and results of Action Research developed by the students of the Technical Institute of Agrarian Reform and Capacitation (RS), that was looking for the development of the professional qualification methodology in strategic for commercialization applied in land and fruits agro industry. The hypothesis of the forces on the market and the use of the societal marketing strategy acknowledge could show them how to build new offers with major added value to commercialize in choose markets who improves with the dependency relation brake by the brokers increasing the salary for this families and by the other hand keeping the principles and values of he MST and Solidary Economy. The results of the participle research showed that in both states the nestings decided by the production lines first and with the raw material in their hand searching for new markets to sale the production and this logical will generate the tentative and error process that is difficult to suppose and with higher cost. The action research results xi showed the societal marketing acknowledge adapted for and improving the economic result and relationship with the market for the studied enterprise.